PENGARUH TERAPI MUSIK GENDING JAWA TERHADAP TINGKAT KECEMASAN PADA PASIEN INTRA OPERASI BENIGN PROSTATIC HYPERPLASIA - Sulastri Wahyuningsih; Anik Suwarni; Atik Aryani (Jurnal Pembangunan dan Kemandirian Kesehatan, 2025)
Background: Benign Prostate Hyperplasia (BPH) is a non-cancerous enlargement of the prostate gland caused by aging and usually occurs in more than 50% of men aged 50 years and over. Medical treatment for BPH patients is Transurethral Resection of the Prostate (TURP) surgery, which can cause anxiety in patients. One way to reduce patient anxiety is Javanese gending music therapy. Objective: To determine the effect of Javanese gending music therapy on the level of anxiety in intra-operative benign prostatic hyperplasia patients. Method: This study used a quantitative approach with the pre-experimental type and with a One Group Pretest-Posttest Design research design. The instrument used the Hamilton Rating Scale For Anxiety (HARS). The sample was patients with benign prostatic hyperplasia surgery at Diponegoro Dua Satu Klaten Hospital with 49 respondents. The sampling technique used purposive sampling. Data analysis used the paired t-test. Results: Most respondents have a level of anxiety before being given music therapy, they have a moderate level of anxiety with 41 respondents (83.7%), while after being given music therapy, most respondents have a mild level of anxiety with 30 respondents (61.2%). Based on the results of the analysis, a p-value of 0.001 <0.05 is obtained. It shows that there is an effect of Javanese gending music therapy on the level of anxiety in intraoperative benign prostatic hyperplasia patients. Conclusion: There is an effect of Javanese gending music therapy on the level of anxiety in intraoperative benign prostatic hyperplasia patients Keywords: Benign Prostatic Hyperplasia, Javanese Gending, Anxiety   ABSTRAK   Latar Belakang : Benigna Prostat Hyperplasia merupakan pembesaran kelenjar prostat non kanker disebabkan oleh penuaan yang biasanya muncul pada lebih dari 50% laki-laki yang berusia 50 tahun ke atas.Penanganan medis pada penderita BPH dilakukan tindakan pembedahan disebut Transurethral Resection of the Prostate (TURP) yang dapat menimbulkan kecemasan pada pasien. Salah satu cara mudah untuk mengurangi kecemasan pada pasien adalah dengan menggunakan terapi musik gending jawa. Tujuan : Mengetahui pengaruh terapi musik gending jawa terhadap tingkat kecemasan pada pasien intra operasi benign prostatic hyperplasia. Metode : Penelitian ini menggunakan pendekatan kuantitatif dengan jenis Pre Eksperimental dan dengan rancangan penelitian One Group Pretest-Posttest Design. Instrumen yang digunakan Hamilton Rating Scale For Anxiety (HARS). Sampel penelitian ini adalah pasien yang menjalani operasi benign prostatic hyperplasia di RSU Diponegoro Dua Satu Klaten sebanyak 49 responden. Teknik pengambilan sampel menggunakan purposive sampling. Analisis data dilakukan dengan uji paired t-test. Hasil : Sebagian besar responden memiliki tingkat kecemasan sebelum diberikan terapi musik memiliki tingkat kecemasan sedang sebanyak 41 responden (83,7%), sedangkan setelah diberikan terapi musik sebagian besar responden memiliki tingkat kecemasan ringan sebanyak 30 responden (61,2%). Berdasarkan hasil analisis diperoleh p-value 0.001 < 0.05 yang menunjukkan terdapat pengaruh terapi musik gending jawa terhadap tingkat kecemasan pada pasien intra operasi benign prostatic hyperplasia. Simpulan : Terdapat pengaruh terapi musik gending jawa terhadap tingkat kecemasan pada pasien intra operasi benign prostatic hyperplasia Kata Kunci : Benign Prostatic Hyperplasia, Gending Jawa, Kecemasan